ANALISIS PENGARUH PROGRAM CSR (CORPORATE SOCIAL RESPONSIBILITY) PERUSAHAAN TERHADAP PEMBERDAYAAN MASYARAKAT PEDESAAN DI KECAMATAN TAPUNG HILIR KABUPATEN KAMPAR (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to analyze the influence of Company’s Corporate Social Responsibility (CSR) programs for community empowerment in Tapung Hilir Kampar District. Research is classified into the type of survey, and using quantitative methods to test the hypothesis. Based on the total population of 2082 families and a sample of 95 people by using simple random sampling technique. Data analysis used descriptive analysis with multiple linear regression analysis. Community empowerment is influenced by CSR programs economic, social and environmental aspects. The results of study showed that either partially or simultaneosly the CSR programs in economic, social and environmental aspects has a significant effect on community empowerment, with 71,5% contributions and the rest is influenced by other factors not examined in this study including CSR programs in legal, ethical and contribution on social issues aspects.Key Words: Corporate Social Responsibility (CSR), Community Empowerment.